Evaluación técnico-financiera de la implementación de brocas policristalinas con cuerpo de acero en la sección de 8 1/2 pulgadas en dos pozos del Campo Acordionero (2018)
The general information about the field is presented, including its location, history and litoestratigraphic information, describing de formations found throughout the drilling of the wells in the Acordionero Field. General information about bits is presented, with a further emphasis in PDC bits, where there is shown their characteristics, details and design variables. PDC with matrix body and steel body are presented, introducing their main characteristics and differences between them. Data and results from de Acordionero-8 and Acordionero-9 in their 8 1/2 inches are presented, these wells where drilled with PDC matrix bits. Later, the same data and results are presented from the Acordionero-11 and Acordionero-12, drilled with PDC steel bits. A technical comparison is made between the results acquired with the matrix and steel body PDC bits, using this data on a new theoretical well, to reach a more representative comparison. Finally, a financial evaluation is made with the ''CAUE'' indicator on the previous data and results, getting as a result a reduction in total and effective times, as well as the costs in the operation when the steel body PDC bit is applied instead of the matrix body one.